Non-financial Incentives for Retention of Health Extension Workers in Somali Region of Ethiopia: A Discrete Choice Experiment - Olusola Oladeji; Andrew Brown; Maritza Titus; Maria Muniz; Alex Collins; Janet Muriuki; Bibilola Oladeji; Yejimmawork Ayalew; Ann Robins (SAGE Publishing, 2022)
The study evaluated non-financial incentive packages to retain health extension workers in the Somali Region of Ethiopia using the Discrete Choice Experiment (DCE) technique, conducted among 66 health extension workers in 3 woredas (districts). The study used a mix of qualitative and quantitative methods in sequential order. Mixed logic regression modeling was used to determine the effect of different job attributes on the retention of the health extension workers, while Preference Impact Measure (PIM) was used to determine the combinations of preferred incentive packages to retain the health extension workers in their current workplace. Opportunity for continued education ranked first, 1.009 (0.655, 1.36), P  = .000, followed by career advancement/opportunity for promotion, 0.321 (0.107, 0.534), P  = .003, then supportive management 0.234 (−0.395, −0.073), P  = .004. in terms of impact on retention. The most preferred incentive package for retention using the PIM model was opportunities for continued education after 3 years and always good availability of and access to amenities (running water, electricity, internet), which predicted a 77% retention rate if implemented. The identified proposed retention incentive packages will help in developing evidence-based incentive policies and strategies for the future retention of health extension workers in this region.